2015
DOI: 10.1021/acsbiomaterials.5b00181
|View full text |Cite
|
Sign up to set email alerts
|

High and Low Molecular Weight Hyaluronic Acid Differentially Influence Macrophage Activation

Abstract: Macrophages exhibit phenotypic diversity permitting wide-ranging roles in maintaining physiologic homeostasis. Hyaluronic acid, a major glycosaminoglycan of the extracellular matrix, has been shown to have differential signaling based on its molecular weight. With this in mind, the main objective of this study was to elucidate the role of hyaluronic acid molecular weight on macrophage activation and reprogramming. Changes in macrophage activation were assessed by activation state selective marker measurement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
400
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(441 citation statements)
references
References 100 publications
11
400
5
3
Order By: Relevance
“…It is reported that hyaluronic acid (HA) has immunotoxicological effect on macrophages, which can activate macrophages and increase the production of endogenous reactive oxygen species (ROS). 20,21 Herein, we question whether HA has the ability to shape the inflammatory behavior of TAMs and contribute to macrophage polarization. Furthermore, to improve the biocompatibility of MnO 2 NPs, we conjugated HA to polyelectrolyte-coated MnO 2 NPs and obtained HA-MnO 2 NPs (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that hyaluronic acid (HA) has immunotoxicological effect on macrophages, which can activate macrophages and increase the production of endogenous reactive oxygen species (ROS). 20,21 Herein, we question whether HA has the ability to shape the inflammatory behavior of TAMs and contribute to macrophage polarization. Furthermore, to improve the biocompatibility of MnO 2 NPs, we conjugated HA to polyelectrolyte-coated MnO 2 NPs and obtained HA-MnO 2 NPs (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Actually, different reactive oxygen species involved in the degradation process lead to different chemically modified HA oligomers, which are the ones involved in inflammation [75,76]. Low molecular weight fragments of HA tend to be pro-inflammatory, whereas high-molecular weight fragments have anti-inflammatory effects [77]. Crosslinking with DVS increases the molecular weight of HA chain scission fragments, and, actually, several DVScrosslinked HA products are approved for human use (references in the introduction).…”
Section: Discussionmentioning
confidence: 99%
“…400.000-600.000 Da). It is well known that biological effect of HA could be influenced by its molecular size [30]. In the trial of Schlesinger IGA score improved by 65.5% (4 weeks of treatment).…”
Section: Discussionmentioning
confidence: 99%